Visitor Engagement through Location-Sensitive Mobile Applications: The Case for Object-Focused Interpretive Tools - Dimaraki , Evangelia (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2022)
Location-sensitive mobile applications are ideally suited for providing visitors with appropriate interpretive tools to develop their confidence in relating, both intellectually and emotionally, with cultural objects that they encounter in the museum. Object-focused interpretive tools are conceived on the assumption that the target cultural content can be intrinsically engaging, if visitors are supported to perform interpretive acts that illuminate its significance to them. Such tools can also support more demanding participatory activities that invite visitors to contribute their own perspective to the museum narrative, both by easing visitors' reluctance to participate and by scaffolding the generation of more substantial content that is valuable to the institution and to other visitors.